THE INVOLVEMENT OF AFRICA IN THE ADMINISTRATION OF THE ONE BELT ONE ROAD INITIATIVE: AN ANALYSIS - Gimba, Zainab (International Journal of Research -GRANTHAALAYAH, 2018)
The paper examines the new Chinese global initiative of the one belt one road, looking at the new Silk Road from the administrative and beneficial connectivity. Using the secondary methodology, findings show that, the initiative has not really included Africa in its connection, as only Kenya and Egypt are fully integrated. The paper concludes that Africa needs more representation and inclusivity to have a very inclusive global initiative. The paper also recommends that, china should not make Africa and other Asian nations dumping grounds for its finished goods, among other things.